A comparison of two common emotions: personal and historical nostalgia - Marchegiani, Chris (School of Marketing, Curtin Business School, 2010)
This research examines the differences in emotional responses of 806 respondents experiencing Personal or Historical Nostalgic reactions to advertising appeals using an experimental research design. Five emotions common to both conditions are revealed and significant changes in intensity of these emotions are examined. As hypothesized, Upbeat / Elation, Loss / Regret, and Warm / Tender related emotions are significantly more intense under the Personal Nostalgic condition compared to the Historical. However, Negative / Irritation and Serenity / Calm related emotions did not significantly alter. This research highlights the need to treat Nostalgia as two separate appeals and provides insight useful to practitioners about consumer's reactions to each specific appeal. It also suggests the need for future research into Personal and Historical Nostalgia's effect on various other consumer behavior responses.